(untitled) (American Journal of Technology and Applied Sciences, 2022)
In these difficult years, goods of the national economy were delivered only to the Autonomous Soviet Socialist Republic of Karakalpakstan, Khorezm and Toshavuz regions along the Amudarya River. The rapid economic development of the Central Asian republics required a radical improvement of the technical condition of the fleet and its replenishment. It was unthinkable to carry out the growing volume of cargo without it.